A Comparison of Folinic Acid, Fluorouracil and Irinotecan (FOLFIRI) plus Bevacizumab and FOLFIRI plus Aflibercept as Second-line Treatment for Metastatic Colorectal Cancer. Issue 8 (August 2022) - Jo, H.; Lee, M.-S.; Lee, Y.-P.; Kim, H.; Hong, J.Y.; Lee, J.; Park, S.H.; Park, J.O.; Park, Y.S.; Lim, H.Y.; Kang, W.K.; Kim, S.T.
Abstract: Aim: To compare the efficacy and safety of folinic acid, fluorouracil and irinotecan (FOLFIRI) plus bevacizumab or aflibercept in metastatic colorectal cancer (mCRC) patients pretreated with oxaliplatin-based chemotherapy. Materials and methods: We analysed the treatment outcomes of patients receiving FOLFIRI in combination with bevacizumab or aflibercept as second-line treatment for mCRC between October 2017 and March 2020. This analysis included 67 patients receiving FOLFIRI plus aflibercept and 83 receiving FOLFIRI plus bevacizumab. Results: The overall response rate (ORR) was 13.6% (95% confidence interval 4.85–22.34) in the FOLFIRI–aflibercept group and 14.7% (95% confidence interval 6.68–22.71) in the FOLFIRI–bevacizumab group. This difference in ORR was not statistically significant. The median progression-free survival was 8.6 months in the FOLFIRI–bevacizumab group and 8.5 months in the FOLFIRI–aflibercept group ( P = 0.752). Patients in the FOLFIRI–bevacizumab group showed a median overall survival of 12.4 months, whereas patients in the FOLFIRI–aflibercept group had a median overall survival of 13.7 months ( P = 0.276). There were no significant differences in survival between the two treatment groups. The adverse events were also largely similar between the two groups. However, hypertension of grade 3 or more was more frequent in the FOLFIRI–aflibercept group. Conclusion: FOLFIRI plus bevacizumab and FOLFIRI plus aflibercept had similar anti-tumour activities and toxicity profiles when used as second-line therapy in mCRC patients. Based on these data, both aflibercept and bevacizumab are suitable anti-angiogenic agents when used in combination with FOLFIRI for mCRC. Highlights: To compare the efficacy and safety of FOLFIRI plus bevacizumab or aflibercept in mCRC. FOLFIRI–bevacizumab and FOLFIRI–aflibercept showed similar clinical efficacy. The toxicity profiles were also largely similar between the two groups. Both aflibercept and bevacizumab are suitable anti-angiogenic agents when used with FOLFIRI.